Proximity and intimacy with homosexuals: what (dis)embarrassment? - Hélder Meireles Cardeira; Lisete dos Santos Mendes Monico (INFAD, 2014)
This study aims to analyze the embarrassment degree due to the proximity and intimacy with people with a homosexual orientation. We conducted a study with a non-probabilistic sample, through an online questionnaire involving 695 subjects, 215 males and 477 females, aged 17 to 60 years. We applied the Rejection at Proximity/Intimacy Scale [30], and we also collected information about beliefs in God, religiousness level and a several sociodemographic variables. The results show that the biggest source of embarrassment is due to the possibility of having a homosexual son/daughter. Men have higher levels than women, and age has a little influence on levels of embarrassment with proximity/intimacy with homosexuals. The religion showed to have a significant weight in the embarrassment levels, evidencing Catholics and individuals from minority religions with higher levels, as opposed to atheists. The embarrassment levels showed themselves positively associated to belief in God and the religiousness level in people.